1999
DOI: 10.1021/jp991445g
|View full text |Cite
|
Sign up to set email alerts
|

G2(MP2) Molecular Orbital Study of [H3AlXH3]- (X = C, Si, and Ge) and H3AlYH3 (Y = N, P, and As) Complexes

Abstract: [H3AlXH3]- (X = C, Si, and Ge) and H3AlYH3 (Y = N, P, and As) have been investigated as donor−acceptor complex types at the G2(MP2) level of theory. Both staggered and eclipsed conformations have been examined. For all complexes, the first one is found to be favored. The G2(MP2) results show that the anionic complexes are more stable than the neutral ones. They show also that this stability decreases when going from carbon to germanium for [H3AlXH3]- complexes and from nitrogen to arsenic for H3AlYH3 complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 40 publications
4
31
0
Order By: Relevance
“…The same trend has been observed in the [H 3 AlXH 3 ] -(X ) C, Si, and Ge) and H 3 AlYH 3 (Y ) N, P, and As) hydrogenated complexes. 29 Concerning the bond angles ∠C-X-Al and ∠C-Y-Al, there is no notable deviation between the two compound sets. For the anionic ones, the MP2(full)/6-31G(d) optimized values are 110.5°, 115.0°, and 116.3°(Table 1) for [H 3 AlC(CH 3 ) 3 ] -, [H 3 AlSi(CH 3 ) 3 ] -, and [H 3 AlGe(CH 3 ) 3 ] -, respectively, while in the free ligand [X(CH 3 ) 3 ] -, this angle is 111.3, 120.7, and 121.6°f or [C(CH 3 ) 3 ] -, [Si(CH 3 ) 3 ] -, and [Ge(CH 3 ) 3 ] -, respectively.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The same trend has been observed in the [H 3 AlXH 3 ] -(X ) C, Si, and Ge) and H 3 AlYH 3 (Y ) N, P, and As) hydrogenated complexes. 29 Concerning the bond angles ∠C-X-Al and ∠C-Y-Al, there is no notable deviation between the two compound sets. For the anionic ones, the MP2(full)/6-31G(d) optimized values are 110.5°, 115.0°, and 116.3°(Table 1) for [H 3 AlC(CH 3 ) 3 ] -, [H 3 AlSi(CH 3 ) 3 ] -, and [H 3 AlGe(CH 3 ) 3 ] -, respectively, while in the free ligand [X(CH 3 ) 3 ] -, this angle is 111.3, 120.7, and 121.6°f or [C(CH 3 ) 3 ] -, [Si(CH 3 ) 3 ] -, and [Ge(CH 3 ) 3 ] -, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…32,33 The QMOA arguments have proven useful and successful for predicting the broad outlines of calculations. [29][30][31][32][33] The choice of the complexes investigated was made with the aim to include different types of strongly bound molecules (anionic one) and coordination compounds (neutral one). To the best of our knowledge, no comparative study of these complexes has been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…However, the C Me -Al-C Me angles clearly pass from D 3h in free metallane to T d in the complex, implying covalent Sn-Al bond character, which parallels results of theoretical investigations for the model compounds [H 3 AlEH 3 ] − (E = C, Si, Ge). 14…”
Section: Lanthanoid(ii) Complexes Of Sn-m Bonded Adductsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24] Recently, we reported a detailed ab initio molecular orbital studies of a series of donor-acceptor complexes of AlH 3 . [25][26][27][28] We showed that the stability of these complexes does not depends on the charge transfer. We have also shown that the donor-acceptor interaction was note based on a simple HOMO-LUMO mixture.…”
Section: Introductionmentioning
confidence: 99%